Functional significance of eIF5A and its hypusine modification in eukaryotes - Park, M. H.; Nishimura, K.; Zanelli, Cleslei Fernando [UNESP]; Valentini, Sandro Roberto [UNESP] (Springer, 2010)
The unusual basic amino acid, hypusine [N(epsilon)-(4-amino-2-hydroxybutyl)-lysine], is a modified lysine with the addition of the 4-aminobutyl moiety from the polyamine spermidine. This naturally occurring amino acid is a product of a unique posttranslational modification that occurs in only one cellular protein, eukaryotic translation initiation factor 5A (eIF5A, eIF-5A). Hypusine is synthesized exclusively in this protein by two sequential enzymatic steps involving deoxyhypusine synthase (DHS) and deoxyhypusine hydroxylase (DOHH). The deoxyhypusine/hypusine synthetic pathway has evolved in archaea and eukaryotes, and eIF5A, DHS and DOHH are highly conserved suggesting a vital cellular function of eIF5A. Gene disruption and mutation studies in yeast and higher eukaryotes have provided valuable information on the essential nature of eIF5A and the deoxyhypusine/hypusine modification in cell growth and in protein synthesis. In view of the extraordinary specificity and functional significance of hypusine-containing eIF5A in mammalian cell proliferation, eIF5A and the hypusine biosynthetic enzymes are novel potential targets for intervention in aberrant cell proliferation.
Keywords: Hypusine; eIF5A; Posttranslational modification; Polyamine; Deoxyhypusine synthase; Deoxyhypusine hydroxylase; Gene inactivation